Experimental simulation study of rockburst characteristics of Sichuan–Tibet granite: A case study of the Zheduoshan tunnel - Liu, Dongqiao; Ling, Kai; Guo, Changbao; He, Pengfei; He, Manchao; Sun, Jie; Yan, Xiaohai (Engineering geology, 2022)
Rockburst poses a great threat to the construction safety of deep tunnels under high geostress conditions. Recently, numerous deeply buried tunnels have been constructed in China, especially in the Sichuan–Tibet railway area. In this study, two rockburst experiments (strainbursts and impact-induced rockbursts) were conducted under different initial geostresses using the strainburst experimental apparatus and impact-induced rockburst experimental apparatus equipped with an acoustic emission (AE) monitoring system. A video acquisition system was used to capture the rockburst process. The results demonstrated that the rockburst process is similar under different initial geostresses, including grains ejection, rock plates spalling/buckling, and fragments ejecting violently. Based on the result of the AE characteristics, the large- amplitude AE signals were concentrated in the lower frequency band and the rockburst intensity was increased gradually with increase in the initial geostress. The b-value and βt-value fluctuated slightly at first, subsequently increased steadily, and then decreased abruptly when rockburst occurred. Furthermore, the displacement and divergence fields on the specimen surface were calculated using digital image correlation (DIC) technology. The result shows that the zone of large deformation and high divergence is consistent with the rockburst zone. Moreover, 80%σpeak is a critical stress state where rocks begin experiencing slight damage. •Failure process of strainbursts and impact-induced rockbursts is reproduced in laboratory.•Frequency-amplitude characteristics of AE under different geostress are analyzed.•Evolution of b-value and βt-value during the experiments is investigated.•Deformation and divergence fields are calculated, and microcracks begin to initiate and propagate at 80% of the peak stress.